2016
DOI: 10.18632/oncotarget.9643
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia potentiates the cytotoxic effect of piperlongumine in pheochromocytoma models

Abstract: Hypoxia is a common feature of solid tumors that activates a plethora of pathways, resulting in proliferation and resistance of cancer cells to radio- and chemotherapy. Pheochromocytomas/paragangliomas (PHEOs/PGLs) with mutations in the gene coding for the subunit B of succinate dehydrogenase (SDHB) are the most aggressive forms of the disease, which is partially due to their pseudohypoxic character, metabolic abnormalities, and elevated reactive oxygen species (ROS) levels. We investigated the effect of piper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Concerning these data, it seems that a weak deleterious effect of hypoxia, when combined with other pro-apoptotic factor(s), may represent a decisive element leading to pancreatic β-cell death. Potentiation of the cytotoxic effect of various agents due to hypoxia was published in other cell types [21,22]. We have also shown that hypoxia strongly decreased the protective effect of unsaturated OA against the pro-apoptotic effect of saturated SA.…”
Section: Discussionsupporting
confidence: 71%
“…Concerning these data, it seems that a weak deleterious effect of hypoxia, when combined with other pro-apoptotic factor(s), may represent a decisive element leading to pancreatic β-cell death. Potentiation of the cytotoxic effect of various agents due to hypoxia was published in other cell types [21,22]. We have also shown that hypoxia strongly decreased the protective effect of unsaturated OA against the pro-apoptotic effect of saturated SA.…”
Section: Discussionsupporting
confidence: 71%
“…GFAP density used the “moments” thresholding method at 95% for the measurement. Microglia projection length was measured using the built-in measurement tool and scaling to convert pixel to μm as previously described [22]. Purkinje cells were counted by measuring the number of calbindin positive cell bodies with a recognizable dendritic tree or axonal projection remaining within a given cerebellar lobule.…”
Section: Methodsmentioning
confidence: 99%
“…PC-12 is a rat pheochromocytoma cell line of neuroendocrine origin derived from the adrenal glands. This cell line has been used as a model system to evaluate the cytotoxic and neurotoxic effects of various substances (14)(15)(16). We used PC-12 cells to elucidate the mechanism underlying the anticancer effects of UA.…”
mentioning
confidence: 99%